Elite survey of the bridging project: "The political sociology of cosmopolitanism and communitarianism". Technical report - Céline Teney; Oliver Strijbis; Sarah Carol; Senem Tepe (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
This elite survey has been carried out as part of the data collection effort of the WZB bridging project "The Political Sociology of Cosmopolitanism and Communitarianism". Elites from five countries that were selected to represent five world regions (Germany, Poland, Turkey, Mexico and USA) compose the cross-national samples. Moreover, we included a sample of elites working at the EU and global levels. For each of these seven cases, we sampled positional elites working in the following 12 societal sectors: politics, administration, justice, military and police, labor union, lobbyism, finance and economy, research, religious institutions, civil society, culture and media. We applied the same positional approach to identify elites at the national, European and global levels: elites are defined as the persons holding the highest positions in the most influential organizations within societal sectors. The sample design allows thus the comparison of elites at the same level across sectors and elites from the same sector across levels (i.e., national, European and global). The questionnaire focuses on denationalization issues that are most likely to be contested by actors on a cosmopolitan/communitarian ideological dimension: regional integration (border crossing of authority), immigration (border crossing of people), human rights (border crossing of norms), climate change (border crossing of pollutants) and international trade (border crossing of goods). One further objective of this elite survey was to enable elite-mass attitudinal comparison on the five denationalization issues across the five countries. Therefore, we included in the questionnaire items that were administered in cross-national mass surveys. All in all, the sampling and questionnaire designs of this elite survey enable three different types of analysis: (1) national and crossnational comparative analysis of the opinions of elites on the five denationalization issues across sectors of activity; (2) cross-level comparison of the attitudes of elites working at the national, EU and global levels across sectors of activity; and (3) analysis of the elitemass gap in attitudes toward denationalization issues in the five countries. We used a mixed-mode approach for the data collection and contacted elites by combining personalized emails, personalized letters and telephone reminders. The data collection took place from spring 2014 until spring 2015. In total, 1604 completed questionnaires were collected. This paper discusses the sampling and questionnaire designs, response rates and data cleaning. It also presents the list of variables available from these survey data.
Keywords: 300; Cosmopolitanism; Communitarism; Elites